Odpowiedzi

2010-02-02T19:06:23+01:00
A)3x+4-x/5=x-1 | razy 5
15 x + 20 - x = 5x - 5
15x - x - 5 x = -5 - 20
9x = - 25 | : 9
x = - 2 i 7/9

b)5(3-x)+x-3/2=4x+5 | razy 2
10(3-x) + 2x - 3 = 8x + 10
30 - 10 x + 2x - 3 = 8x + 10
10x + 2x - 8x = 10 - 30 + 3
4x = - 17 | :4
x = - 6,25

c)2(5-x)-7-x/2=x-1 | razy 2
2(5-x) - 14 - x= 2x - 2
10 - 2x - 14 - x = 2x - 2
2x - x - 2x = -2 -10 +14
-x = 2 | :(-1)
x = -2

d)x-1/3-x-2/2=2x-5/6 |razy 6
6x - 2 - 6x - 6 = 12 x - 5
6x - 6x - 12x = -5 +2 + 6
- 12x = 3 | : (-12)
x = - 1/3

e)x+6/2-5+x/3=2-x/6 | razy 6
6x + 18 - 30 + 2x = 12 -x
6x + 2x + x = 12 - 18 + 30
9x = 24 | : 9
x = 2 i 2/3

f)2x-3/6 -8-x/9=x+3/18 | razy 18
36 x - 9 - 144 - 2x = 18x + 3
36 x - 2x - 18x = 3 + 9 + 144
16 x = 156 | : 16
x = 9,75

nie jestem pewna, czy nie zrobiłam jakichs błedów, więc sprawdź dla pewności :)